Amaryllis - Sydney Park Brown; Robert J. Black (EDIS)
Revised! Circular 1243, a 4-page fact sheet by Sydney Park Brown and Robert J. Black, describes this subtropical bulb with large trumpet shaped flowers which is popular with Florida gardeners — its landscape uses, planting, general care, propagation, and disease and pest management. Includes references. Published by the UF Department of Environmental Horticulture, October 2007.